Invertebrates in Science Communication: Confronting Scientists’ Practices and the Public’s Expectations - Salvador, Rodrigo B.; Tomotani, Barbara M.; O’Donnell, Katrin L.; Cavallari, Daniel C.; Tomotani, João V.; Salmon, Rhian A.; Kasper, Julia (Frontiers in Environmental Science, 2021)
Good science communication should give the public the tools to make informed decisions and take action, which can be particularly important for nature conservation. The crisis in invertebrate conservation might be rooted in public prejudices against invertebrate animals, which are perceived as the unpopular 97% of Earth’s animal biodiversity. As such, how we approach science communication regarding those animals might yet play a critical role in their conservation. Given how specialized a topic invertebrate biology is, a large part of its communication fall to scientists. Here, we surveyed both scientists and members of the public about the former’s approaches and assumptions and the latter’s interest and expectations regarding invertebrate science communication, confronting the results of each survey. Our findings show that scientists and the public are only tangentially aligned; there is plenty of ground scientists and communicators need to pay attention to and explore better in order to achieve more meaningful and balanced science communication. Our results have unveiled some issues and are thus a good first approach to start defining the way forward.